PENGARUH MOTIVASI KERJA DAN KOMPETENSI KERJA TERHADAP KINERJA PEGAWAI DINAS KEBUDAYAAN KOTA MEDAN - Bena Br Ginting (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
This research was conducted to find out how Work Motivation and Work Competence Toward Performance of Medan City Culture Department Employees. This study uses three variables consisting of Performance variables namely Employees (Y), while the independent variables are Work Motivation (X1) and Work Competence (X2). This type of research is explanatory research through associative research, namely research that aims to explain the difference between two or more variables. The population in this study were all employees of the Medan City Culture Office received 38 civil servants. The method of data collection is done by literature study questionnaire, and observation. Data analysis conducted in this study was hypothesis testing with t test (partial test) and F test (simultaneous test). The results showed that: (1) based on partial tests of Motivation Influenced the performance of Medan City Culture Department employees with a t test of 3.721. (2) Based on a partial competency test on the performance of Medan City Culture Department employees with a t test of 4.073. (3) Based on the Simultaneous test the Effect of Work Motivation and Work Competence on the Performance of Medan City Culture Office Employees with an F test of 62.332.